Pricing strategies of Online Stores and its influence on Consumers’ buying decision. - Dr. Waqar Ahmad (The Retail and Marketing Review, 2025)
There is a direct correlation between the pricing and the amount of money a business makes. It has a long-term impact on the company's revenue, earnings, and investments, and it is the central variable in its financial models. Pricing reveals how a company thinks and acts in relation to its rivals and the value it provides to its consumers. A pricing strategy is monitoring the market and making adjustments to the price of products and services as needed. When formulating a pricing plan, several factors are taken into account, such as research, market conditions, customer willingness to pay, competition, trade margins, expenses, etc. The purpose of this research was to analyse pricing tactics as a component that impacts consumers' final purchasing decisions. Using a modified questionnaire derived from scholarly sources, the current study employed quantitative research methods. A total of 174 online shoppers made up the sample for this investigation. Information collected from the city of Erbil in the Kurdistan region, Iraq using a random sample technique. There was strong evidence of convergent and discriminant validity in the questionnaire's components, as well as good internal consistency and reliability of scale items, according to factor loading, Cronbach's alpha, composite reliability, average variance extracted, and correlations. Model fit indices showed that measurement and structural models tying purchase decisions to pricing strategies such competitive pricing, bundle pricing, dynamic pricing, and penetration pricing were well-fit with the data. The structural model's path analysis revealed that competitive pricing, bundle pricing, dynamic pricing, price skimming, and penetration pricing all have a role in the purchase decision. An examination of the structural model's path analysis revealed that, among the factors impacting purchase decisions, bundled pricing is more acceptable as compared to penetration, competition, skimming, and dynamic pricing. Consumers' purchasing decisions are favorably affected by bundle pricing followed by competitive pricing, dynamic pricing, price skimming, and penetration pricing.